Effects Of Carbonated and Energy Drinks on Human Health - Sattarova Barnokhon; Begaliyev Nurillo (Genius Journals, 2022)
This article discusses the effects of strong carbonated and energy drinks on human health.
Keywords: Tourin; caffeine; theobromine; melotanin